PENGOLAHAN LIMBAH CAIR TAHU MENJADI BIOGAS RUMAH TANGGA DI DESA KUNCEN - Oktavianus Cahya Anggara; Aditya Yanuariski; Bayu Ali Syahbana; Muhamad Alfian; M. Ibnu Tantowi; Muhammad Nurfauzi; Yunia Rifatul Umah (Politeknik Negeri Sriwijaya, 2023)
The tofu industry plays a crucial role in providing a vital plant-based protein source for the community; however, it often has significant environmental consequences due to its liquid waste. This waste contains organic substances, proteins, fats, and suspended particles that pollute water ecosystems. The high organic content diminishes oxygen levels in the water, endangering aquatic life and damaging water and soil quality in Kuncen Village, a tofu production hub. An intriguing solution involves converting tofu liquid waste into biogas through anaerobic organic decomposition. This research evaluates the potential of processing tofu liquid waste into biogas as a sustainable household energy source in Kuncen Village. The objective is to mitigate the environmental impact of tofu waste while providing an eco-friendly energy alternative. The study encompasses experiments and analyses with a focus on measuring gas volumes from the biogas installation. Although initial trials have not yielded sufficient gas production, this research provides valuable insights into making the tofu liquid waste-to-biogas process more efficient and sustainable.